Implikasi Pengaturan Lingkungan Hidup terhadap Peraturan Perundang-Undangan dalam Kegiatan Bisnis (Perspektif Konstitusi) - Muhammad Insa Ansari (The Constitutional Court of the Republic of Indonesia, 2014)
In the Act of 1945 (before amendment) environment is part and Chapter XIV of the National Economy and Social Welfare, precisely in Article 33 paragraph (3). After the amendment, the environment gets the settings in Chapter XA of Human Rights, which in Article 28H (1) and Chapter XIV of the National Economy and Social Welfare, which in Article 33 paragraph (3) and (4). Environmental settings in the constitution of course have implications for legislation, including legislation business activities. There are a number of regulations of business activities that have included environmental material in it. Law No. 40 of 2007 on Limited Company is a business law institutions that have incorporated environmental material. While the laws governing business activities have included environmental material of which is Law No. 25 of 2007 on Investment, Law No. 10 of 1998, and a number of other legislative business activities.